A simply triggered peptide-based hydrogel as an injectable nanocarrier of tanshinone IIA and tanshinones. Issue 3 (14th December 2016) - Yin, Yajun; Wu, Can; Wang, Junling; Song, Fengjuan; Yue, Wanqing; Zhong, Wenying
Abstract : An easily self-assembled and gelated octa-peptide FHFDFHFD was chosen as a novel drug delivery system (DDS) for both tanshinone IIA and total tanshinone extract. Abstract : An easily self-assembled and gelated octa-peptide FHFDFHFD was chosen as a novel drug delivery system (DDS) for both tanshinone IIA and total tanshinone extract. The DDS showed increased loading capacity, sustained drug release and better anticancer capability. Our research proved that a hydrogel DDS of other traditional Chinese medicines is possible.